Elie Wiesel : Jewish, literary, and moral perspectives - Katz, Steven T., 1944-; Rosen, Alan (Alan Charles) (Bloomington, Indiana : Indiana University Press, 2013)
Nobel Peace Prize recipient Elie Wiesel, best known for his writings on the Holocaust, is also the accomplished author of novels, essays, tales, and plays as well as portraits of seminal figures in Jewish life and experience. In this volume, leading scholars in the fields of Biblical, Rabbinic, Hasidic, Holocaust, and literary studies offer fascinating and innovative analyses of Wiesel's texts as well as illuminating commentaries on his considerable influence as a teacher and as a moral voice for human rights. By exploring the varied aspects of Wiesel's multifaceted career-his texts on the.
Part 5. Legacies20. With Shadows and With Song: Learning, Listening, Teaching; 21. Teaching through Words, Teaching through Silence: Education after (and about) Auschwitz; 22. Toward a Methodology of Wonder; 23. Wiesel's Contribution to a Christian Understanding of Judaism; 24. Conscience; Contributors; Index.
Title from PDF title page (viewed on May 14, 2013).
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 600
Keywords: Wiesel, Elie, -- 1928-2016 -- Criticism and interpretation; Wiesel, Elie, -- 1928-; Wiesel, Elie, -- 1928-2016; Humanistic ethics; Jewish ethics; Holocaust, Jewish (1939-1945) -- Influence; Holocaust, Jewish (1939-1945) -- Moral and ethical aspects; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- Jewish; Ethics; Humanistic ethics; Influence (Literary, artistic, etc.); Jewish ethics; 1939-1945; Electronic books; Criticism, interpretation, etc